2022
DOI: 10.1186/s12909-022-03347-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Problem-Based Learning implementation in a College of Medicine, Kingdom of Saudi Arabia: a cross sectional comparative study

Abstract: Background Problem-Based Learning (PBL) is an innovative student-centered learning method that has been implemented in numerous medical colleges worldwide. However, the newly adopting PBL institutes may face challenges during its implementation. This study aims to evaluate PBL implementation in the medical college of Imam Abdulrahman bin Faisal University (IAU) from the facilitators’ and students’ perspectives. Methods This is a cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
1
3
1
Order By: Relevance
“…In our study females were more satisfied on the problem and the session as compared with males but this was not statistically significant which is in contradiction to another study in Saudi Arabia where females' satisfaction on problem-based learning was higher where they discussed the implications of teaching at different facilitators and different campuses [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study females were more satisfied on the problem and the session as compared with males but this was not statistically significant which is in contradiction to another study in Saudi Arabia where females' satisfaction on problem-based learning was higher where they discussed the implications of teaching at different facilitators and different campuses [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Effective tutor is one which stimulates situated collaborative active learning [13]. Overall, students were satisfied with the tutor's facilitation skills who provided constructive feedback and intervened when needed as supported by another study in Saudi Arabia [12]. They were satisfied with the tutors' enthusiasm, support, and respect for the learning process.…”
Section: Discussionmentioning
confidence: 95%
“…Learning objectives also lack integrity of different disciplines and do not promote collaborative learning. Studies in Saudi Arabia, Ghana, and Egypt also revealed similar findings [ 7 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 59%
“…[8,27–30] Our results are similar to previous reports that students who have experienced integrated PBL will develop a desire for knowledge and possess the ability to actively analyze and solve problems, which will benefit them for a lifetime. [25,31] In sum, this study proved that integrated PBL combined with LBC had effects on students’ knowledge acquisition and competency development, and could improve their comprehensive abilities to learn independently, to raise, analyze and solve problems, which are necessary for being a doctor in the future.…”
Section: Discussionmentioning
confidence: 73%